Work performance and its influencing factors among support staff in Hospital Mersing, Johor - Faiz Daud; Siti Norbani A; Azimatun Noor Aizuddin; Nik Azlan Nik Muhamad (Pusat Perubatan Universiti Kebangsaan Malaysia, 2020)
Work performance report is a systematic and comprehensive evaluation report that quantitatively assesses the level of performance of civil servants in Malaysia. The objective of this study was to ascertain whether work performance of supporting staff in Hospital Mersing is at par with the performance of civil servants in Malaysia. Other objectives were to identify the high-performing and lowperforming members in the organisation and to determine factors affecting work performance. This study was a cross-sectional, retrospective, and used convenient sampling from secondary data in the employee service books, Human Resource Management Information System (HRMIS) information and staff medical records in 2016. The results of this study show that there was significant relationship between socio-demographic factors with work performance, which were gender, monthly income and education level. However, there was no significant relationship between ethnicity (p=0.692), age (p=0.102), marital status (p=1.000) and period of service (p=0.299). There was no significant relationship found between health factor and job factor with work performance. The outcome from this study can be used by the hospital administration and supervisors to take measures improving the level of staff work performance accordingly, which can benefit both individual and the organisation.